Total phenolics, toxicity and antimicrobial activity of the essential oil of the leaves of Alpinia zerumbet (Pers.) B.L. Burtt & R.M. Sm (Research, Society and Development, 2020)
This study aimed to determine total phenolics, assess toxicity and antimicrobial activity of essential oil (EO) of Alpinia zerumbet leaves. The EO was extracted by hydrodistillation and the physicochemical parameters were determined according to the Brazilian Pharmacopoeia. The toxicity assay followed the lethality bioassay against the non-target organism Artemia salina Leach. The antimicrobial activity followed the methodology described by the Clinical and Laboratory Standards Institute using the Method of Disc Diffusion and Broth Dilution to determine the Minimum Inhibitory Concentration (MIC) for the action of EE against Escherichia coli, Staphylococcus aureus, Aspergillus sp. and Penicilium sp. OE yield was 0.71%. Lethal Concentration 50% (LC50) for the action of EO against Artemia salina L. 280.40 mg/L, being considered nontoxic. Through the antimicrobial assays, the OE presented bactericidal activity against the bacteria E. coli and S. aureus,and fungicide activity against the fungi Aspergillus sp. and Penicillium sp. It was concluded that the EO has a good antimicrobial potential, and its application is appreciated by its classification as nontoxic OE..